How Global Are Local Value Chains? - Alessandro Borin; Francesco Paolo Conteduca; Fabrizio Leone; Michele Mancini; Patrick Zoi (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper examines how international trade shocks transmit through domestic supply chains, shaping local economic vulnerabilities. Using detailed firm-to-firm domestic and foreign transaction data, we quantify the direct and indirect exposure of Italian labor markets to two major sources of external risk: imports from China and exports to the United States. We quantify the importance of firms' domestic and foreign linkages for overall exposure and highlight the critical role of wholesalers and top trading firms within the domestic network in shaping tails risks. Pronounced local disparities in exposure reveal that aggregate trade statistics conceal substantial and uneven regional vulnerabilities.
Keywords: F14; R12; L14; F61; R15; 330; global value chains; local labor markets; trade shocks; firm-to-firm linkages; geopolitical fragmentation; production network